HOW WELL DO MOTHERS UNDERSTAND WHY THEIR NEWBORN IS HOSPITALIZED? - Kafle, Raju; Gupta, Binod Kumar; Agrawal, Nikhil (Journal of Universal College of Medical Sciences, 2016)
INTRODUCTION: Maternal knowledge about serious infant illnesses has significant implications for care after discharge, particularly in countries with high infant mortality rates. No existing studies on this topic in low income countries were identified. The study sought to identify the level of maternal understanding about why a newborn was hospitalized and how mothers attributed blame for the illness. MATERIAL AND METHODS: We conducted semi-structured interviews with mothers aged 18 and older who had infants hospitalized in a tertiary care facility in Universal College of Medical Sciences, Bhairahawa, Nepal and collected data on demographics, pregnancy and delivery, and beliefs about their infant's illness. Infant charts were abstracted to identify medical reasons for hospitalization for comparison with the mother's understanding, and levels of understanding were coded as 'none', 'partial' or 'full'. RESULTS: One hundred and fifty three mothers were interviewed and their average age was 28. For 27%, this was their first pregnancy. Forty per cent of mothers had no understanding of why their infant was in the hospital and 28% had only partial understanding. One-third of the women reported blaming themselves for the child's illness. In multivariable analysis, demographic factors including maternal age, education, primiparous status, and urban vs rural residence did not predict maternal understanding or self-blame. CONCLUSIONS: Sick newborns in low-income countries are at very high risk of adverse outcomes. Mothers who lack a clear understanding of why their infant is in the hospital might have difficulty communicating preferences about care, understanding the type of care that is being given, and recognizing future warning signs of illness. Such gaps in understanding could put the discharged infant at significant risk. Journal of Universal College of Medical Sciences (2015) Vol.03 No.02 Issue 10